RETHINKING HIGHER EDUCATION SERVICES AND THE COMPLAINT HANDLING FRAMEWORK IN MALAYSIA (UUM Journal of Legal Studies, 2023)
In the last few decades, Malaysia has become a global hub for higher education services. Policies and programs have been put in place to improve the higher education system in the country and attract more international students. This development needs to be aligned with an effective dispute resolution framework to ensure the continuous development of the Malaysian higher education sector. The methodology employed in this paper is a doctrinal method based on the nature of the discourse. To examine the relevant higher education concepts and dispute resolution framework, research papers pertinent to the subject were analysed. In addition, relevant legislations were consulted to determine the adequacy of the existing legal framework for dispute resolution in the higher education context in Malaysia. The main objective of this paper is to examine the nature of education services and the existing dispute resolution mechanisms in the Malaysian higher education sector. The paper will explore education services as either a "public good" or a "private good" and whether students are consumers in the real sense and have consumer rights. This research establishes that although scholars have often argued as to whether or not students are consumers, in Malaysia and other Asian countries, students are perceived as customers, and therefore, the interest, welfare and satisfaction of students must always be of utmost priority. A thorough study of the existing laws reveals that there is an inadequate provision in the education laws in Malaysia, especially regarding the mechanisms of dispute resolution in its higher education institutions.